Influence of Full Oral Feeding Acquisition on Growth of Premature Infants - Chinea Jiménez, Bibiana; Ferrández Ferrández, Silvia; Díez Sebastián, Jesús; Saenz de Pipaon, Miguel (Frontiers in Pediatrics, 2022)
Objective: The main objective was to describe the impact of full oral feeding achievement in very low birth weight infants on weight, length, and head circumference, measured as the change in z-score from 32 weeks to discharge, the time at which full oral feeding occurs. Methods: This was a longitudinal retrospective observational study on infants younger than 30 weeks of gestational age, admitted to the Neonatology Unit of La Paz University Hospital, Madrid (Spain), from 1 January 2019 to 31 December 2019. The infant's anthropometric characteristics (weight, height, head circumference) were compared at birth, at 32, 34, and 36 weeks of gestational age, at the time of full oral feeding, and at discharge from the unit. Results: 66 infants were included, gestational age at birth range from 24 to 30. Full oral intake occurred at 37.1 ± 2.1 weeks postmenstrual age (PMA). We found an inverse correlation between gestational age at birth and birth weight with PMA at which full oral feeding (FOF) is achieved. PMA at discharge was 38.6 ± 2.5 weeks. Age of full oral intake and discharge occurred later in infants who had patent ductus arteriosus, retinopathy of prematurity and, sepsis or received a blood transfusion. A positive correlation was found between days of oxygen and both parameters. However, we found no relationship between necrotising enterocolitis or intraventricular haemorrhage with age at full oral feeding or age at discharge. Conclusions: The transition from gastric tube to oral intake did not affect growth. We found a close relationship between preterm infants birth, earlier younger than 30 weeks of gestational age, and low birth weight, with a delay in full oral feeding achievement that correlated with age at discharge.